Describing the on-the-job training experiences of bachelor of science in management accounting students - Ailyn Bernido; Melbert Palapas; Sanny Earl Casera; Genesis Naparan; Janus Naparan (Journal of Management and Business Education, 2024)
This study aims to describe the on-the-job training experiences of BSMA students at Saint Columban College, Pagadian City. A single case study was most appropriate for the research’s proper conduct since this study wants to describe and understand the on-the-job training of BSMA students who experience this program. The findings led the researchers to the conclusion that the research participants described their on-the-job training as a journey of learning, growth, and application of their academic knowledge to the real-world context of accounting and management fields. They expressed a sense of practicality and hands-on learning, emphasizing the transition from theoretical concepts to practical applications. Their narratives show the importance of concrete experiences within their training, followed by reflective observations that allow them to derive meaningful insights. The development of abstract conceptualizations and stage of active experimentation highlights the value of these experiences in shaping their professional skills and development.